Thyrotoxicosis followed by hypothyroidism in a patient on lithium - Nilamadhab Kar (Mental Illness, 2014)
While hypothyroidism is common in lithium-treated patients, thyrotoxicosis is rarely reported. We present a female patient on lithium for maintenance therapy of bipolar affective disorder, who developed thyrotoxicosis for few months which was followed by hypothyroidism which continued. There was no further thyrotoxicosis episode during a five year follow up period. While she was treated for thyroid dysfunction, lithium was continued. There was no clinical impact on the maintenance of the bipolar affective disorder during the follow up period; she was maintained well in the community.